PENANGGULANGAN STRES ANAK MELALUI PEMBELAJARAN (PAK) KELAS X DI SMA RK SERDANG MURNI LUBUK PAKAM - Sembiring, Mimpin; Ginting, Rania Betesda Br; Simbolon, Erikson (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Stress and the management of student stress are crucial issues in the field of education, especially at the high school level. Grade X students at SMA RK Serdang Murni Lubuk Pakam experience academic stress caused by heavy workloads, grade competition, exam anxiety, and uncertainty about their future education. This stress affects students cognitively, affectively, behaviorally, and physiologically, which in turn disrupts their learning process. This study aims to examine how stress is managed among Grade X students and how Catholic Religious Education (PAK) contributes to the coping process. This research employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The subjects were Grade X students and the Catholic Religion teacher. The findings show that stress management is facilitated through spiritual guidance, moral motivation, and reflective activities such as prayer and sharing, led by the PAK teacher. The PAK learning materials, particularly